Nutritional Status Of Dairy Cattle In Kupwara District Of Kashmir) - Bhat, Sajad. H.; Mattoo, F. A.; Medhi, D.; Ahmad , H. A.; Afzal, Y. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A survey was conducted in nine villages, three each from Kupwara, Handwara and Karnah tehsils of Kupwara district to ascertain the existing feeding practices and nutritional status of dairy cattle. Fifteen farm families from each nine villages were randomly selected and data were collected through a common questionnaire. The average land holdings (ha/family) of the farmers was 0.80±0.02, 2.49±0.08 and 0.89±0.05 in Kupwara, Handwara and Karnah tehsils, respectively The average body weight (kg) of lactating cows was 205.78±6.81, 196.83±4.90 and 176.58±2.75 in Kupwara, Handwara and Karnah tehsils respectively. The daily intake of concentrates (kg) and roughages (kg) for lactating cows were 4.43±0.27 and 4.47±0; 4.97±0.21 and 5.60±0.38; 3.34±0.16 and 3.70±0.34 in Kupwara, Handwara and Karnah tehsil, respectively. Average daily DM intake for lactating cows was in excess to the tune of 19.61 and 43.93 per cent for Kupwara and Handwara tehsils while for Karnah tehsil it was deficit by 4.74 per cent. The daily DCP intake was 12.65 and 38.10 per cent surplus than their requirement in Kupwara and Handwara tehsils while in Karnah tehsil, it was deficit by 5.22 per cent. The daily TDN intake was 36.70, 55.9 and 7.6 per cent in excess to their nutrient requirements for the respective tehsils. The daily average milk yield (lt./ animal/day) was 4.89 ±0.37, 4.69±0.28 and 3.76±0.28 in the respective tehsils. Milk urea nitrogen was 18.55±0.74, 21.29±1.31 and 16.87±1.41 for the respective tehsils.
Keywords: Nutritional Status; Lactating Cattle; District Kupwara; Kashmir